Desarrollo de cuatro preparaciones gastronómicas a base de chayote - Cuamacás Balenzuela, Kennyn Remigio (2025)
The present study addresses the potential of chayote (Sechium edule) in gastronomy, a underutilized product despite its notable nutritional benefits and versatility. Through this research, the aim is to diversify its use by creating four innovative preparations that promote its consumption. The identified problem lies in its limited culinary use, representing an opportunity to explore its integration into modern and healthy recipes. The general objective is to develop preparations that highlight the organoleptic properties of chayote and assess its acceptance among consumers and experts. The methodology combines qualitative and quantitative approaches. Surveys were used to measure the acceptance of the preparations, interviews with experts were conducted to obtain technical recommendations, and indirect observation was employed to evaluate interaction with the dishes. The culinary techniques included sautéing, pickling, baking, and fresh presentations. Data were collected in Ibarra, Ecuador, considering a representative sample of 166 participants and gastronomy experts. Among the most relevant results, four gastronomic preparations were designed: stuffed chayote, pickles, ceviche, and chayote in wine. These recipes stood out for their texture, flavor, and versatility, being well-appreciated for their balance between innovation and nutrition. Surveys reflected a high interest in main dishes and desserts, while interviews highlighted the acceptance of chayote as an accessible and healthy ingredient. It is concluded that chayote, being a healthy and accessible ingredient, has the potential to position itself as an attractive option for consumers interested in innovative gastronomic alternatives.